Современные трансформации правового обеспечения международной морской торговли - Липинская, А.А. (Економічні інновації, 2009)
В статті розглядаються основні питання щодо спрощення процедур міжнародної морської торгівлі у світі. Спрощення процедур торгівлі є взаємовигідним напрямком зусиль, що може принести реальні вигоди, як для уряду, так і для ділових кіл і може стати важливим фактором підвищення конкурентоспроможності у морській торгівлі. In the article basic questions are examined in relation to simplification of procedures of international sea-born trade in the world. Simplification of trade procedures is mutually beneficial direction of efforts of, which can bring the real benefits, both for a government and for business communities and can become the important factor of increase of competitiveness in sea-born trade.